APLIKASI GAME SIMULASI OPERASIONAL SUPERMARKET DENGAN CREATE JS DI PT HARJA GUNATAMA LESTARI - Hendi Suhendi; Angga Pratama; Haris Supriatna (STMIK Mardira Indonesia, Bandung, 2021)
The supermarket that is currently growing rapidly is a shopping mall that provides daily necessities. The large number of visitors resulted in a surge in operations that made the supermarket must always be ready, fast, precise, and experienced. Simulation is useful to train employees in solving the problem, then created this supermarket simulation game application aims to hone the skills of each employee. The creation of this simulation game application author using methods (R&D), analysis of software and hardware needs, questionnaires about jobdesk and problems that occur, storyboard design, and will be tested with white-box testing techniques. The resulting simulation game application is a 2-dimensional game whose performance is exactly the same as the fact that happened in the supermarket itself, the challenge in this simulation game is that each player must survive in handling every consumer who keeps coming, control every movement of goods, speed up the cashier service in the transaction process, and always control the availability of goods. With this, the author hopes to the store manager to be more reliable in handling every problem so that consumers also get a pleasant shopping experience. Keyword : Simulation games, supermarkets, web applications, employees.DOI: 10.5281/zenodo.5784154